PERCEPTION OF WORKING ONLINE VERSUS OFFLINE AMONG ACADEMIC PROFESSIONALS - Soonthodu, Sachin; Rao, Nagarjuna (International Online Journal of Education and Teaching, 2020)
COVID- 2019 is a challenge for the survival of humans and the society. Business organizations are facing the worst hit due to continuous lockdown. Education institutions and the universities are facing a tough time to balance teaching-learning effectiveness. Many education institutions have adopted online technology with optimum utilization of available resources; others face a tough time for survival. This study aims at understanding teachers’ perception towards offline and online teaching. 480 academic professionals were selected based on simple random sampling techniques. Paired sample T test and One-way ANOVA is used to study and find out the difference in the perception of working online and offline among academic professionals. The study finds significant differences in teachers’ perception of offline and online teaching among the academic professionals.